Prophylactic efficacy of recombinant interferon alfa-2b in pregnant women during their stay in the family with SARS-CoV-2 infection: prospective study - Sergey P. Sinchikhin; Lusine V. Stepanyan; Elena V. Proskurina; Onsi Nasri; Ekaterina S. Sinchikhina (IP Berlin A.V., 2022)
Background. The high contagiousness and susceptibility of a pregnant woman's body to a new coronavirus infection requires study not only of etiopathogenesis, but also of developing methods to prevent the development of this disease. Aim. To evaluate the preventive effectiveness of the use of a drug containing recombinant interferon alfa-2b (IFN-a2b) and an antioxidant complex in pregnant women during their stay in the family focus of a new coronavirus infection. Materials and methods. 75 pregnant women were under observation, in whose family there were patients infected with the virus that causes a new coronavirus infection. Treatment of sick relatives was carried out at home, as the disease in them proceeded in an uncomplicated form. The main group was formed by 37 pregnant women who treated the nasal mucosa with a preparation containing recombinant IFN-a2b in the amount of 5000 IU and an antioxidant complex (alpha-tocopherol acetate, citric and benzoic acids). The comparison group was formed by 38 pregnant women who did not use any drugs for prophylactic purposes. All patients observed generally accepted rules of personal hygiene and behavior. The duration of prophylactic use of the indicated medicinal product depended on obtaining a negative result for the causative agent of a new coronavirus disease, an infected family member. A smear from the nasopharynx and oropharynx was examined to detect SARS-CoV-2 RNA by PCR once every 57 days. Results. COVID-19 vaccination did not exclude infection with the SARS-CoV-2. Preventive treatment of the nasal mucosa with an IFN-a2b containing drug reduced the risk of infection with this viral agent in vaccinated patients who were in household contact with a patient with COVID-19 by 6 times. Asymptomatic and mild course of a new coronavirus infection was observed in 3 (25%) and 7 (58.3%) patients of 12 infected women from the main group and in 8 (22.9%) and 18 (51.4%) patients of 35 infected women from the comparison group, respectively. Further local use of the drug containing recombinant IFN-a2b and an antioxidant complex contributed to a decrease in the duration of infection and the course of the disease. Progression of COVID-19 was observed in unvaccinated patients with concomitant somatic pathology (diabetes mellitus, iron deficiency anemia, cardiovascular diseases, etc.): 2 (16.7%) and 9 (25.7%) people in groups, respectively. Conclusion. The use of recombinant IFN-a2b with an antioxidant complex in pregnant women with a family focus of new coronavirus infection is clinically appropriate and highly effective.